Da gui mo shu ju fen xi he jian mo : ji yu Spark yu R = Mastering Spark with R - Luraschi, Javier; Kuo, Kevin; Ruiz, Edgar (O'Reilly jing pin tu shu xi lie., 2020)
Detailed summary in vernacular field.